La etnología chiriguano de Alfred Métraux - Federico Bossert; Diego Villar (Journal de la Société des Américanistes)
The Chiriguano Ethnology of Alfred Métraux. The paper analyzes the influence of Erland Nordenskiöld and Marcel Mauss on the early academic, intellectual and professional career of Alfred Métraux. In a broader perspective it focuses on the theoretical and methodological influence of French sociology and the Scandinavian school of Americanist ethnology on Métraux’s first researches on historical and living Tupi-Guarani groups, particularly the Tupinamba and Chiriguano. We pursue our analysis across diverse aspects of Métraux’s work, including: his treatment of religion and prophetism among the Tupinamba; his participation in the pioneer project that created the Ethnology Institute in Tucuman; the manifestation of ideology, inherited prejudice and esthetic values in his gathering of material culture collections; the singularities of Métraux’s fieldwork and its impact on his relationship with the Chiriguano; his thesis that Chiriguano pottery reflected particular mixtures of Andean, Chaco and Amazonian influences; and, finally, the significant link he found between mythic symbolism and the feminine universe.